The Impact of Climatic Factors on Grain Crop Yields in Uzbekistan - Rustamova, Iroda; Galimova, Firuza; Dekhkanova, Nilufar; Madiev, Shakhzod; Turgunova, Gulchekhra (International Journal of Energy Economics and Policy, 2026)
This article is dedicated to analyzing the impact of climate change on grain crop yields in Uzbekistan between 1991 and 2023. The main objective of the work is to establish how temperature fluctuations and precipitation affect the short-term and long-term yield dynamics. The study used the ARDL econometric model, which allows us not only to identify short-term changes but also to track how yield indicators adjust over time. To determine the reliability of the model results, stability tests were conducted using the Augmented Dickey-Fuller and P-P tests, which allowed for the use of both source and transformed data. The model results indicate that temperature has a positive effect on yield both in the short and long term. The impact of precipitation in the short term is not statistically significant; however, its lagged effect is negative. That is, a high level of precipitation in the previous year may adversely affect yield in the following year. In the model (ARDL 1,0,1) selected by the BIC criterion, the delayed temperature value is not included, but the main effect is retained. The model selected under the AIC criterion (ARDL 1,1,1) gives a more accurate result as it also includes the delayed temperature effect, although it is shown not to be statistically significant. This study contributes to the existing body of literature by using this model which analyse the short-run and long-run relationships between different time series variables. The originality lies in that the results of the ARDL model based on two different scenarios in studying the impact of climatic factors on grain crop yields in our country, as well as their validation using a number of diagnostic tests, fully meet all requirements for all criteria. On this basis, it is possible to fully utilise this model. The findings of this study hold significant practical value for policymakers anf agricultural economists in Uzbekistan. Under the conditions of global climatic changes, the wide use of econometric research methods in the study of agricultural production processes will contribute to decision-making on sustainable development of the agriculture and achievement of high efficiency.